The influence of sofiiski elements on the formation of the spiritual world of a person. (Journal of Educational Sciences, 2016)
In this article the author deals with an influence of the Islam on the formation of the spiritual world of a person. The authors note that the remnants of the Sufi elements in Eastern literature, including the works of Kazakh poets Shakarim Kudaiberdiev and Mashhur Zhusup Kopeyev affect the spiritual development of personality. Indeed, the world of Islam boundless and limitless. Crucial to the definition and disclosure of the content of the work, written in the spirit of Islam, on the way to the Truth. The article notes, it is necessary, first, to determine and indicate the spirit of Turkish literature, and secondly, the approach of modern society to the religion of Islam. The article emphasizes that under the poetics and quatrains lurk deep thoughts, spiritual values, the theme of the sophistic literature is love. Therefore, the authors emphasize that today requires attention to the spiritual Outlook problem because, the deeper they penetrate into the depths of the Islamic world, and can be found in the pearl of thought.
Keywords: islam; spirituality; humanism; spiritual values; Sufi poetry; the Eastern tradition